Continuous electrodermal activity as a potential novel neurophysiological biomarker of prognosis after cardiac arrest – A pilot study. (August 2015) - Alvarez, Vincent; Reinsberger, Claus; Scirica, Benjamin; O'Brien, Molly H.; Avery, Kathleen R.; Henderson, Galen; Lee, Jong Woo
Abstract: Aims: Neurological outcome prognosis remains challenging in patients undergoing therapeutic hypothermia (TH) after cardiac resuscitation. Technological advances allow for a novel wrist-worn device to continuously record electrodermal activity (EDA), a measure of pure sympathetic activity. Methods: A prospective cohort study was performed to determine the yield of continuous EDA in patients treated with TH for coma after cardiac arrest during hypothermia and normothermia. Association between EDA parameters (event-related and nonspecific electrodermal responses (ER-EDR, NS-EDR)) and outcome measures (cerebral performance category [CPC]) (Full Outline in UnResponsivenss (FOUR) score) were assessed. Results: Eighteen patients were enrolled. Total number of EDR (66.4 vs 12.0/24 h, p = 0.02), ER-EDR (39.5 vs 11.2/24 h, p = 0.009), median amplitude change of all EDR (0.08 vs 0.03 μSI, p = 0.03) and ER-EDR (0.14 vs 0.05 μSI, p = 0.025) were higher in patients with favorable (CPC 1–2) versus poor outcome (CPC 3–5) during hypothermia. Greater differences in EDA parameters were observed during hypothermia than normothermia. The FOUR score was correlated to the number of all EDR and median amplitudes. Conclusions: Continuous EDA potentially opens a new avenue for autonomic function monitoring in neurocritically ill patients. It is feasible in the ICU setting, even during hypothermic states. As a measure of a complete neurophysiological circuit, it may be a novel neurophysiologic biomarker of outcome after cardiac resuscitation.